Identifikasi larva Aedes aegypti dan Aedes albopictus di Kecamatan Pahandut Kota Palangka Raya - Sabira, Zahra; Jabal, Arif Rahman; Ratnasari, Arini; Toemon, Agnes Immanuela; Hanasia (Tropis: Jurnal Riset Teknologi Laboratorium Medis, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by Aedes spp. mosquitoes. which can be found in tropical and sub-tropical climates. The transmission of dengue fever is closely related to people's daily living habits. Factors that play a role in the emergence of disease are influenced by human factors as hosts and Aedes spp mosquitoes. as a vector for transmitting dengue fever. The breeding place for Aedes spp. can increase the mosquito population in transmitting dengue fever to humans. Research on peat water as a habitat for Aedes spp. larvae. It is very important to do this as an effort to control dengue vectors, especially in areas where the pH of the water tends to be acidic in Palangka Raya City because the larvae of Aedes spp. has the ability to adapt to water that tends to be acidic. This research was conducted using a survey method with a cross-sectional study and experimental laboratory design.